From Bush Medicine to Modern Phytopharmaceutical: A Bibliographic Review of Devil's Claw (Harpagophytum spp.) - Thomas Brendler (MDPI AG, 2021)
Devil's claw (Harpagophytum spp., Pedaliaceae) is one of the best-documented phytomedicines. Its mode of action is largely elucidated, and its efficacy and excellent safety profile have been demonstrated in a long list of clinical investigations. The author conducted a bibliographic review which not only included peer-reviewed papers published in scientific journals but also a vast amount of grey literature, such as theses and reports initiated by governmental as well as non-governmental organizations, thus allowing for a more holistic presentation of the available evidence. Close to 700 sources published over the course of two centuries were identified, confirmed, and cataloged. The purpose of the review is three-fold: to trace the historical milestones in devil's claw becoming a modern herbal medicine, to point out gaps in the seemingly all-encompassing body of research, and to provide the reader with a reliable and comprehensive bibliography. The review covers aspects of ethnobotany, taxonomy, history of product development and commercialization, chemistry, pharmacology, toxicology, as well as clinical efficacy and safety. It is concluded that three areas stand out in need of further investigation. The taxonomical assessment of the genus is outdated and lacking. A revision is needed to account for intra- and inter-specific, geographical, and chemo-taxonomical variation, including variation in composition. Further research is needed to conclusively elucidate the active compound(s). Confounded by early substitution, intermixture, and blending, it has yet to be demonstrated beyond a reasonable doubt that both (or all) Harpagophytum spp. are equally (and interchangeably) safe and efficacious in clinical practice.